2017
DOI: 10.5944/openpraxis.9.4.724
|View full text |Cite
|
Sign up to set email alerts
|

Effect of “Tell Me More” on EFL Undergraduate Students’ English Language Achievement

Abstract: This descriptive study aimed at finding the impact of Tell Me More (TMM), an online language-learning program, on English as a foreign language (EFL) undergraduate learners' achievement in a University in Thailand. The study also looked at whether the time of use of TMM had an effect on learners' achievement. Data was collected from the scores of students at four proficiency levels who did the placement, progress and achievement tests in the TMM program for the 2015 academic year. The analysis of the data indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…The content of TMM has been structured around authentic events like at the airport, weather forecast, a linguistic function, and listening to a dialogue on scenarios of communication. This is followed by an activity of interaction and other pronunciation, standard activities of vocabulary and grammar (Gyamfi & Sukseemuang, 2017).…”
Section: Review Of the Literature Backgroundmentioning
confidence: 99%
“…The content of TMM has been structured around authentic events like at the airport, weather forecast, a linguistic function, and listening to a dialogue on scenarios of communication. This is followed by an activity of interaction and other pronunciation, standard activities of vocabulary and grammar (Gyamfi & Sukseemuang, 2017).…”
Section: Review Of the Literature Backgroundmentioning
confidence: 99%
“…A descriptive study on undergraduate students' achievement with TMM at four proficiency levels revealed an improvement in the proficiency level of beginners and advanced users (Gyamfi & Sukseemuang, 2017). Interestingly, TMM had no to little impact on the English proficiency of students at the intermediate+ and intermediate levels.…”
Section: Related Studiesmentioning
confidence: 99%